2010
DOI: 10.1039/c0nr00446d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous CuO–CeO2 nanospheres with an enhanced low-temperature CO oxidation activity

Abstract: CuO-CeO2 nanospheres with a porous structure were synthesized by an improved urea method involving first hydrothermal treatment to get Ce-Cu binary precursor and then the calcination of the precursor. The CuO-CeO2 nanospheres consist of spherical particles with diameters in the range of 300-400 nm. These nanospheres are actually composed of nanoparticles of ca. 10 nm, resulting in the formation of a mesoporous structure. Compared with conventional urea method, in which Ce-Cu binary precursor is commonly achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 39 publications
4
60
0
Order By: Relevance
“…It is well known that larger bulk CuO particles contribute very little or even negatively to the activity for CO oxidation owing to the coverage of active species on the catalyst surface. 7,11,58 Therefore, the lower activity of the 4-CCS and 5-CCS catalysts can be accounted for by the presence of more amounts of larger bulk CuO particles as evidenced by the XRD and Raman characterization results.…”
Section: Activity Of Catalystsmentioning
confidence: 99%
“…It is well known that larger bulk CuO particles contribute very little or even negatively to the activity for CO oxidation owing to the coverage of active species on the catalyst surface. 7,11,58 Therefore, the lower activity of the 4-CCS and 5-CCS catalysts can be accounted for by the presence of more amounts of larger bulk CuO particles as evidenced by the XRD and Raman characterization results.…”
Section: Activity Of Catalystsmentioning
confidence: 99%
“…Jernigan and Somorjai [36] showed that the rate of CO oxidation at 300 • C decreased with increasing copper oxidation state. Qin et al [37] suggested that Cu 2+ was the active site in the CuO-CeO 2 system. Nina Perkas et al [38] indicated that metallic Cu 0 deposited on TiO 2 would enhance its activity in CO oxidation, with the Cu 0 metal serving as both an effective co-catalyst for CO oxidation and a reducing species to react with CO.…”
Section: Introductionmentioning
confidence: 99%
“…Most applications of CuO are focused on the catalytic activity for CO oxidation. Qin et al fabricated porous CuO-CeO 2 nanospheres products to obtain higher catalytic activity [32]. Ma et al reported an improved sol-gel method with incorporation of thermal treatment under N 2 to Cu 1 Ce 8 Fe x -O catalysts for low temperature CO oxidation [33].…”
Section: Introductionmentioning
confidence: 99%